2020
DOI: 10.24251/hicss.2020.248
|View full text |Cite
|
Sign up to set email alerts
|

Here, there, but not everywhere: Adoption and Diffusion of IoT in Swedish Municipalities

Abstract: The Internet of Things (IoT) brings with it promises of smart cities with improved efficiency, increased transparency, and enhanced public services. However, few studies have empirically and systematically investigated the reasoning behind the decision to adopt IoT within municipal organizations. In this paper we study the adoption and diffusion of IoT in Swedish municipalities. We outline areas of application and perceived value creation and conclude that the main reasons for adoption and diffusion can be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The Internet of Things (IoT) is an increasingly important technological paradigm that is considered to be a key enabler of public sector smartness. Data from sensor-based systems can be integrated and synthesised with public services (Kankanhalli et al, 2019;Saarikko et al, 2020), ultimately culminating in the provision of services that are more responsive and accessible to citizens. The public sector can integrate IoT into a vast array of services, such as traffic solutions, effective waste management, optimised administration, and efficient healthcare (Chatfield & Reddick, 2019;Velsberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Internet of Things (IoT) is an increasingly important technological paradigm that is considered to be a key enabler of public sector smartness. Data from sensor-based systems can be integrated and synthesised with public services (Kankanhalli et al, 2019;Saarikko et al, 2020), ultimately culminating in the provision of services that are more responsive and accessible to citizens. The public sector can integrate IoT into a vast array of services, such as traffic solutions, effective waste management, optimised administration, and efficient healthcare (Chatfield & Reddick, 2019;Velsberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the great benefits are found in time and cost reduction. IoT and its purported role in creating smart cities [2,8] has the potential to facilitate the core tenets of lean management, i.e. efficient work processes and effective allocation of resources.…”
Section: Environmental Benefits and Lean Managementmentioning
confidence: 99%
“…A common reason for this is that the top-mounted sensor sometimes registers the litter bin as full if the plastic bin liner is not properly inserted into its metal housing or if an empty/nearly empty bag is pushed to one side by a gust of wind. Even though connected equipment is sometimes referred to as "smart" products [8], sensors can sometimes be remarkably un-smart.…”
Section: Digitalised Work Processes and Social Benefitsmentioning
confidence: 99%
“…The majority of IoT initiatives have thus far been implemented in the private sector, but studies show that IoT adoption is increasing within the public sector as well (Borgia 2014;Neirotti et al 2014;Saarikko et al 2020). Under constant pressure to simultaneously lower costs and increase citizen value, the application of IoT in the public sector is mainly motivated by the possibility to improve efficiency, increase transparency and enhance public services (Saarikko et al 2020).…”
Section: Creating Value With Iotmentioning
confidence: 99%
“…The majority of IoT initiatives have thus far been implemented in the private sector, but studies show that IoT adoption is increasing within the public sector as well (Borgia 2014;Neirotti et al 2014;Saarikko et al 2020). Under constant pressure to simultaneously lower costs and increase citizen value, the application of IoT in the public sector is mainly motivated by the possibility to improve efficiency, increase transparency and enhance public services (Saarikko et al 2020). It is therefore not surprising to see that implemented solutions often focus on areas that are connected with high maintenance costs, such as infrastructure, utilities, transportation, and facility management and on services that are directly addressing citizen needs, such as various applications for health-and self-care.…”
Section: Creating Value With Iotmentioning
confidence: 99%